202k views
1 vote
Factor completely 25x2 − 9.

2 Answers

3 votes

Answer:


(5x+3)(5x-3)

Explanation:

Here the given expression is,


25x^2-9


=(5x)^2-(3)^2

By using identity a² - b² = (a+b)(a-b),


=(5x+3)(5x-3)

Since, further factorization is not possible,

Hence, the required factor form of the given expression is,


(5x+3)(5x-3)

User Morizotter
by
5.2k points
3 votes

Answer:

(5x-3) (5x+3)

Explanation:

25x^2 − 9

This is the difference of squares

a^2 - b^2 = (a-b) (a+b)

let a^2 =25x^2 so a =5x

let b^2 =9 so b= 3

25x^2 -9 = (5x-3) (5x+3)

User Tolotra
by
5.3k points